Tolerância a Falhas em Sistemas Embarcados Baseados em Microcontroladores - Medeiros, Wanderson Ricardo de (2018)
The number of computing systems around us is increasing in a daily basis, turning our society more dependent of the facilities o ered by them. Embedded systems are produced in even more reduced components, and found in several types of equipments and utensils, from clothes to last generation smartphones. This miniaturization is possible due to the advances in chip manufacture techonology. Allowing the fabrication of reduced components, such as microcontrollers, which are entire computing systems embedded in one single chip. Among the di erent types of computing systems, it is important to highlight critical systems. In theses systems, the slightest mistake can cause catastrophic consequences for the users. The use of fault tolerance in computing system design consists in the application of methods and techniques that aim to keep the system workng correctly even in unexpeted situations, cosenquetly, increasing reliability and system robustness. This work aims to include fault tolerance in microcontroller based embedded systems, taking into consideration area restrictions, energy and cost, demosntrating the impact on thoses aspects caused by the techniques.